KESIAPAN PEDAGOGIS DIGITAL GURU DALAM OPTIMALISASI GAMIFIKASI UNTUK PEMBELAJARAN MENDALAM: SYSTEMATIC LITERATURE REVIEW PADA TRANSFORMASI PENDIDIKAN DASAR DI INDONESIA - Lidia Aprileny Hutahaean; Resmi; Perawati Silalahi; Vinda Afnita; I Kadek Satria Arsana; Dominikus Rojoki Manullang (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The digital transformation of Indonesian education post-pandemic has accelerated the integration of gamification as an innovative learning strategy in elementary schools. However, a critical gap persists between gamification implementation and teachers' digital pedagogical readiness, hindering deep learning optimization. This systematic literature review aims to analyze the role of digital pedagogical readiness in optimizing gamification for deep learning within Indonesian elementary education context. Using PRISMA framework, 28 peer-reviewed articles from Google Scholar, SINTA, DOAJ, ERIC, and ScienceDirect (2018-2025) were systematically analyzed through thematic analysis and CASP quality assessment. Findings reveal that Indonesian elementary school teachers' digital pedagogical readiness remains varied, with technological competence being the dominant factor affecting gamification effectiveness. A significant positive correlation exists between teachers' digital pedagogical readiness and gamification success in enhancing student engagement and learning outcomes. Cultural-contextual gamification strategies integrating local values show superior effectiveness compared to generic approaches. The study recommends a TPACK-based teacher training model integrated with Merdeka Mengajar Platform and phased implementation strategies considering infrastructure disparities. These findings provide practical implications for policymakers, school leaders, and teachers to optimize digital transformation in Indonesian elementary education through holistic readiness enhancement and culturally-responsive gamification design.